Association of HbA1c and utilization of internal mammary arteries with wound infections in CABG - Knochenhauer, Tim; Schaefer, Andreas; Brickwedel, Jens; Reiter, Beate; Naito, Shiho; Zipfel, Svante; Schneeberger, Yvonne; Reichenspurner, Hermann; Sill, Bjoern (Frontiers in Cardiovascular Medicine, 2024)
Background Deep sternal wound infection (DSWI) remains a serious complication after coronary artery bypass grafting (CABG). We herein aimed to stratify diabetic patients who underwent CABG using bilateral internal mammary artery (BIMA) for levels of glycated hemoglobin A1C (HbA1c) and compare postoperative outcomes. Methods Between January 2010 and August 2020, 4,186 consecutive patients underwent isolated CABG at our center. In 3,229 patients, preoperative HbA1c levels were available. Primary endpoints were wound healing disorder (WHD), DSWI, and 30-day mortality. Patients were stratified according to preoperative HbA1c levels. Patients were further divided into subgroups according to utilization of BIMA. Results After adjustment, no differences in mortality and stroke rates were seen between group 1 (HbA1c < 6.5%) vs. group 2 (HbA1c ≥ 6.5%). WHD was more frequent in group 2 [2.8 vs. 5.6%; adjusted p = 0.002; adjusted odds ratio (OR), 1.853 (1.243–2.711)] but not DSWI [1.0 vs. 1.5%; adjusted p = 0.543; adjusted OR, 1.247 (0.612–2.5409)]. BIMA use showed a higher rate of WHD [no BIMA: 3.0%; BIMA: 7.7%; adjusted p = 0.002; adjusted OR, 4.766 (1.747–13.002)] but not DSWI [no BIMA: 1.1%; BIMA: 1.8%; adjusted p = 0.615; adjusted OR, 1.591 (0.260–9.749)] in patients with HbA1c ≥ 6.5%. Conclusions Intraoperative utilization of BIMA is not connected with an increase of DSWI but higher rates of WHD in patients with poor diabetic status and HbA1c ≥ 6.5%. Therefore, application of BIMA should be taken into consideration even in patients with poor diabetic status, while identification of special subsets of patients who are at particular high risk for DSWI is of paramount importance to prevent this serious complication.